Experimental investigation of D2 conversion to DHO in soil near the Cernavoda nuclear power plant site in Romania. (February 2021) - Kim, S.B.; Bredlaw, M.; Festarini, A.; Bucur, C.; Popescu, I.; Constantinescu, M.; Bucura, F.; Rousselle, H.; Beaton, D.; Korolevych, V.Y.; Chen, G.; Stuart, M.
Abstract: The current Canadian and Romanian model predictions for tritium dose following an atmospheric tritiated hydrogen gas (HT) release is based on a default Canadian Standards Association (CSA) conversion factor of HT to tritiated water (HTO) of 4.3%. The determination of an empirical site specific value for the conversion factor was essential for the CANDU Cernavoda Nuclear Power Plant (NPP) in Romania to verify if the CSA value is appropriate for use at this site. Given the role of soil characteristics on the conversion of HT to HTO, on-site experiments would provide the best evaluation of the conversion factor. The objective of the study was to define the soil HT to HTO conversion parameters specific to the Cernavoda NPP site. In June 2016, a series of experiments were conducted to meet this objective. First, the in situ deposition velocity of D2 gas, as a surrogate for HT gas, was obtained using an exposure chamber. Diffusion of D2 into the soil was then evaluated based on the measurements of DHO concentrations in the exposed soil. As soil microbes play a role in the conversion of HT to HTO, this work included a microbiological characterization of the soil, which targeted total soil bacteria (cultivable and gene-based) and hydrogen oxidizing bacteria (cultivable and gene-based). The fraction of hydrogen oxidizing cultivable soil bacteria represented 14–20% of the total cultivable bacteria population estimated as 2.8–29.2 × 10 5  cfu/g of soil. The empirically derived HT to HTO conversion factor was lower than the default value (4.3%). It fell between 0.9% and 2.0%. The default value is therefore more conservative than the Cernavoda site-specific derived value obtained from the study. Highlights: The objective of the study was to define the soil HT to HTO conversion parameters specific to the Cernavoda NPP site. Measure hydrogen oxidizing bacteria in soil near the Cernavoda NPP. The empirically derived HT to HTO conversion factor is lower than the default value of 4.3%.